Aerobic exercise is promoted when individual performance affects the group: a test of the Kohler motivation gain effect - Irwin, Brandon C.; Scorniaenchi, Jennifer; Kerr, Norbert L.; Eisenmann, Joey C.; Feltz, Deborah L. (My University, 2012)
Background: A key barrier to achieving recommended intensity and duration of physical activity is motivation. Purpose: We investigated whether a virtually-present partner would influence participants’ motivation (duration) during aerobic exercise. Method: Fifty-eight females (M[subscript age] = 20.54 ± 1.86) were randomly assigned to either a coactive condition (exercising along side another person, independently), a conjunctive condition (performance determined by whichever partner stops exercising first) where they exercised with a superior partner, or to an individual condition. Participants exercised on a stationary bike at 65% of heart rate reserve on 6 separate days. Results: Across sessions, conjunctive condition participants exercised significantly longer (M = 21.89 min, SD = ±10.08 min) than those in coactive (M = 19.77 min, SD = ± 9.00 min) and individual (M = 10.6 min, SD = ± 5.84 min) conditions (p < 0.05). Conclusion: Exercising with a virtually-present partner can improve performance on an aerobic exercise task across multiple sessions.
Keywords: Group performance; Group exercise; Exergame; Köhler effect; Motivation; Exercise partner